2023
DOI: 10.1007/s10803-023-05893-z
|View full text |Cite
|
Sign up to set email alerts
|

The Methodological Quality and Intervention Fidelity of Randomised Controlled Trials Evaluating Social Skills Group Programs in Autistic Adolescents: A Systematic Review and Meta-analysis

Abstract: A systematic review and meta-analysis were utilised to explore the methodological quality, program fidelity, and efficacy of social skills group programs (SSGPs) aiming to support autistic adolescents in navigating their everyday social worlds. The study evaluated the methodological quality and theoretical fidelity of studies, with a random effect meta-analysis conducted to summarise the overall efficacy of SSGP and its effect on social communication and interaction, behavioural/emotional challenges, adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Internationally, Social Skills Group Training (SSGT) programmes are demonstrating efficacy in supporting verbal and cognitively able school-aged autistic children in developing their social skills [4, 5, 6]. Multiple meta-analyses of randomised controlled trials (RCTs) evaluating the efficacy of these programmes in autistic youth report moderate to large effect sizes in achieving personally meaningful social goals, enhancing social skills, social skills knowledge, social participation, and social functioning [4, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Internationally, Social Skills Group Training (SSGT) programmes are demonstrating efficacy in supporting verbal and cognitively able school-aged autistic children in developing their social skills [4, 5, 6]. Multiple meta-analyses of randomised controlled trials (RCTs) evaluating the efficacy of these programmes in autistic youth report moderate to large effect sizes in achieving personally meaningful social goals, enhancing social skills, social skills knowledge, social participation, and social functioning [4, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Among interventions for verbal and cognitively capable school-aged autistic children, Social Skills Group Training (SSGT) stands out as an evidence-based group approach [4, 5, 6]. Multiple meta-analyses of SSGT programmes in randomised controlled trials (RCTs) consistently report moderate to large d -type effects in achieving personally meaningful social goals, enhancing social skills, social skills knowledge, social participation, and social functioning [4, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are related to higher self-esteem, better interpersonal relationships, lower incidence of problem behaviors, and better academic performance [33,34]. These skills are essential for successful adaptation in social situations and may include a variety of behaviors, such as cooperation, assertiveness, empathy, and communication skills, as well as catering to the diversity of the student body [35,36]. It has been observed that students with adequate social skills tend to experience lower levels of anxiety compared to their peers with less developed social skills [37][38][39].…”
Section: Introductionmentioning
confidence: 99%